Improved phase stability of CsPbI2Br perovskite by released microstrain toward highly efficient and stable solar cells. Issue 12 (2nd September 2021) - Zheng, Kanghui; Ge, Jinfeng; Liu, Chang; Lou, Qiang; Chen, Xia; Meng, Yuanyuan; Yin, Xu; Bu, Shixiao; Liu, Cuirong; Ge, Ziyi
Abstract: All‐inorganic perovskite solar cells (PSCs) have developed rapidly in the field of photovoltaics due to their excellent thermal and light stability. However, compared with organic–inorganic hybrid perovskites, the phase instability of inorganic perovskite under humidity still remains as a critical issue that hampers the commercialization of inorganic PSCs. We originally propose in this work that microstrains between the perovskite lattices/grains play a key role in affecting the phase stability of inorganic perovskite. To this end, we innovatively design the π‐conjugated p‐type molecule bis(2‐ethylhexyl) 3, 3′((4, 8‐bis(5‐(2‐ethylhexyl)‐3, 4‐difluorothiophen‐2‐yl)benzo[1, 2‐b:4, 5‐b′]dithiophene‐2, 6‐diyl)bis(3, 3″‐dioctyl[2, 2′:5′, 2″‐terthiophene]‐5″, 5‐diyl))(2E, 2′E)‐bis(2‐cyanoacrylate) (BTEC‐2F) to covalent with the Pb dangling bonds in CsPbI2 Br perovskite film, which significantly suppress the trap states and release the defect‐induced local stress between perovskite grains. The interplay between the microstrains and phase stability of the inorganic perovskite are scrutinized by a series of characterizations including x‐ray photoelectron spectroscopy, photoluminescence, x‐ray diffraction, scanning electron microscopy, and so forth, based on which, we conclude that weaker local stresses in the perovskite film engender superior phase stability by preventing the perovskite lattice distortion under humidity. By this rational design, PSCs based on CsPbI2 Br perovskite system deliver an outstanding power conversion efficiency (PCE) up to 16.25%. The unencapsulated device also exhibits an exceptional moisture stability by retaining over 80% of the initial PCE after 500 h aging in ambient with relative humidity of (RH) 25%. Abstract : This work reports the utilization of π‐conjugated small molecule to release the microstrains in perovskite films, which improves the efficiency and stability of perovskite solar cells.